Retrospective Review of the Short-Term Outcomes of Tracheal resection for Laryngotracheal stenosis at Chris Hani Baragwanath hospital - Makaulule, Ratshili Prince (My University, 2019)
INTRODUCTION: Laryngotracheal stenosis is rare but has become a well-recognized pathological otorhinolaryngological condition. It develops when scar tissue forms in the trachea and larynx. Laryngotracheal stenosis can cause significant morbidity and the management of it is often complex. Tracheal resection with end-to-end anastomosis is a well-recognized surgical procedure performed for treatment of larygotracheal stenosis and has been shown to have great success. AIM: To review the short-term outcomes of tracheal resection for larygotracheal stenosis at the Chris Hani Baragwanath Academic Hospital Otorhinolaryngology Department. METHOD: This was a retrospective study, reviewing 24 patients with larygotracheal stenosis who underwent segmental tracheal resection with end-to-end anastomosis at the Chris Hani Baragwanath Academic Hospital, performed between 2005 and 2015. RESULTS: The study included 24 patients with ages ranging from 18 to 64 years. There were 15 (62.5%) males and 9 (37.5%) females. The causes of larygotracheal stenosis were prolonged intubation in 22 (91.7%) and inhalation burns in 2 (8.3%) patients. Eleven patients (45.8%) had postoperative complications, of which 4 (36.4%) were minor complications and 7 (63.6%) were major complications. The outcomes of surgery were excellent in 13 (54.2%), satisfactory in 8 (33.3%) and unsatisfactory in 3 (12.5%). CONCLUSIONS: Prolonged intubation was found to be the most common cause of larygotracheal stenosis. Tracheal resection for larygotracheal stenosis has been shown to have satisfactory to excellent short-term outcomes in terms of successful decannulation, voice quality, and low morbidity. In our study, the surgery was successful in 21 (87%) patients, which is comparable to success rates shown in the literature. Preoperative tracheostomy and higher degree of stenosis Meyer Cotton (III and IV) were associated with high postoperative complications. Irrespective of the cause, tracheal resection is a good surgical option, for the treatment of patients with severe stenosis and those who have failed treatment from other alternative surgeries.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Medicine in Otorhinolaryngology.” Johannesburg, 2019
Keywords: Thoracic Surgery; Intubation, Intratracheal